PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS BUKU CERITA BERGAMBAR UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPAS KELAS IV SD - Septian, Rudi; Ira Restu Kurnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low understanding of Integrated Natural and Social Sciences (IPAS) concepts among fourthgrade students at SDN Cijengkol 02, Bekasi Regency prompted this research. This study aimed to develop a valid, feasible, and effective picture storybook-based learning medium to improve students’ IPAS conceptual understanding. The research used the Research and Development (R&D) method with the ADDIE model through analysis, design, development, implementation, and evaluation stages. Expert validations in content, media, and language rated the product as highly feasible. Limited and field trials showed significant learning improvement, with N-Gain scores in the high category. Teacher and student responses indicated positive satisfaction with the media. The results confirm that the developed picture storybook is effective as an innovative learning medium to enhance the quality of IPAS learning processes and outcomes in elementary schools.